2008
DOI: 10.1088/0022-3727/41/24/245001
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation behaviour of nanostructured Mn–Zn ferrite

Abstract: Dielectric measurements and modulus analysis have been made to investigate the effects of grain size, frequency and temperature for nanostructured Mn–Zn ferrite. The anomalous frequency dependence of dielectric loss (tan δ) can be attributed to the resonance effect and also to the presence of both n- and p-type charge carriers. The tan δ for 59 and 69 nm grain size samples is found to be an order of magnitude smaller than those of bulk particles. Dielectric relaxation studies using modulus formalism have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 22 publications
4
24
3
Order By: Relevance
“…Additionally, through careful observation we can notice an inflexion in the middle of the increasing real modulus for the samples in between 25 and 100 o C; in the meanwhile, the broad peak mentioned in imaginary modulus shows a depressed behavior in the middle of its peak. This is different from the modulus peak of the kinds of ferrites, including CFO ferrite , Ni-Zn and Mn-Zn ferrites (Sivakumar, , 2008, in which only a clearly and smoothly relaxation behavior was observed. The present behavior indicated that this broad peak is constituted by two incomplete relaxation peaks, which are almost merging together.…”
Section: Electrical Moduluscontrasting
confidence: 78%
See 1 more Smart Citation
“…Additionally, through careful observation we can notice an inflexion in the middle of the increasing real modulus for the samples in between 25 and 100 o C; in the meanwhile, the broad peak mentioned in imaginary modulus shows a depressed behavior in the middle of its peak. This is different from the modulus peak of the kinds of ferrites, including CFO ferrite , Ni-Zn and Mn-Zn ferrites (Sivakumar, , 2008, in which only a clearly and smoothly relaxation behavior was observed. The present behavior indicated that this broad peak is constituted by two incomplete relaxation peaks, which are almost merging together.…”
Section: Electrical Moduluscontrasting
confidence: 78%
“…However, the present films show an abnormal relaxation behavior, remarkably expressed in electric modulus spectra, where the electrode polarization is suppressed. Different from a single modulus peak in other nanostructured ferrites (Sivakumar, 2007a(Sivakumar, , 2007b(Sivakumar, , 2008, a temperature dependent crossover between two peaks are observed, which may be induced by the hybridized microstructure consisting of two kinds of different sized CFO particles. The similar phenomenon reported in multiferroic PZT/CFO layered thin films demonstrated it (Ortega et al, 2008), where two electric modulus relaxations were observed, but both relaxations in this multiferroic material were located at different temperature ranges without any overlapping, which should be attributed to the large property difference between insulted PZT and low resistivity CFO phase.…”
mentioning
confidence: 71%
“…The effect of grain interfaces is more pronounced at lower frequencies, were we observe a higher value of dielectric constant (e 0 ). The space charge polarization occurring at the interfaces at lower frequencies can also contribute to dielectric constant (e 0 ) at low frequencies [8][9][10]. It is also observed from the Fig.…”
Section: Density Measurementsmentioning
confidence: 63%
“…7 depicts the dielectric loss behavior of the NiCr x Fe 2−x O 4 system which shows asymmetrical behavior. In this figure, there is a peak in the power loss owing to the transfer of the maximum electrical energy to the oscillating ions when the frequency of the external AC field is equal to the hopping frequency of the charge carriers [20]. The occurrence of the loss peak in the tanδ versus frequency is associated with the correlation between the hopping conduction mechanism and dielectric behavior of spinel ferrites.…”
Section: Dielectric Constant (ε / ) and Dielectric Loss (Tanδ)mentioning
confidence: 93%